Elementos para una nueva síntesis en los estudios sobre las organizaciones sindicales argentinas bajo el gobierno militar (1976-1983) - Zorzoli, María Luciana (2016)
This paper examines classical interpretations in the field of Social Science of the changes experienced by trade unions during the self-named “Proceso de Reorganización Nacional” military government which ruled the country between 1976 and 1983. This aims to identify problematic areas which have been passed on to this area of study. Its current use shall then be questioned and neglected issues that should be considered will be highlighted in order to build a new synthesis on the effects of the social restructuring experienced during the last dictatorship.